2020
DOI: 10.1136/oemed-2019-106271
|View full text |Cite
|
Sign up to set email alerts
|

Firefighter occupation is associated with increased risk for laryngeal and hypopharyngeal squamous cell carcinoma among men from the Greater Boston area

Abstract: ObjectiveFirefighters are exposed to a wide variety of carcinogens during the line of duty, including several associated with head and neck cancer. Existing studies assessing head and neck cancer risk with firefighting have predominately included occupational cohorts or registry data, which are limited by inability to adjust for smoking and alcohol consumption—major risk factors for head and neck cancer. Our objective was to assess the risk of head and neck cancer among men with an occupational history as a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Forest fire will produce a consistent smoke especially in dry season [7]. Study in Boston found that firefighter was the person who susceptible to laryngeal malignancy although there is no history of smoking [14]. Some other profession who have high risk were gasoline station worker, wood processing worker, toxic dust exposure, and mineral industry worker [15].…”
Section: Discussionmentioning
confidence: 99%
“…Forest fire will produce a consistent smoke especially in dry season [7]. Study in Boston found that firefighter was the person who susceptible to laryngeal malignancy although there is no history of smoking [14]. Some other profession who have high risk were gasoline station worker, wood processing worker, toxic dust exposure, and mineral industry worker [15].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with studies conducted in other countries, such as Scotland (Ide, 2014) and Australia (Glass et al, 2017), which found that firefighters had a higher risk of cancer incidence and mortality, particularly for melanoma and kidney cancers. Additionally, a case-control study conducted in the US found that firefighters had a significantly increased risk of head and neck cancer compared to the control group, and this risk was even higher among professionals with longer duration of employment and a history of smoking (Langevin et al, 2020). Finally, a cohort research in the US, including female firefighters, found an increased risk of cancer incidence and mortality, particularly for respiratory, digestive, and urinary cancers, with an excess of mortality due to breast and bladder cancer within the female group (Daniels et al, 2014).…”
Section: Cancer Riskmentioning
confidence: 99%
“…These results are consistent with studies conducted in other countries, such as Scotland (Ide, 2014) and Australia (Glass et al, 2017), which found that firefighters had a higher risk of cancer incidence and mortality, particularly for melanoma and kidney cancers. Additionally, a case-control study conducted in the US found that firefighters had a significantly increased risk of head and neck cancer compared to the control group, and this risk was even higher among professionals with longer duration of employment and a history of smoking (Langevin et al, 2020). Finally, a cohort research in the US, including female firefighters, found an increased risk of cancer incidence and mortality, particularly for respiratory, digestive, and urinary cancers, with an excess of mortality due to breast and bladder cancer within the female group (Daniels et al, 2014).…”
Section: Cancer Riskmentioning
confidence: 99%